2007
DOI: 10.1016/j.childyouth.2006.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Kinship foster parents' perceptions of factors that promote or inhibit successful fostering

Abstract: A better understanding of kinship foster families' perceptions of the familial factors and parenting beliefs that promote or inhibit successful fostering can inform child welfare practice and policy. To this end, and to extend previous research [Buehler, C., Cox, M. E., and Cuddeback, G. (2003). Foster parents' perceptions of factors that promote or inhibit successful fostering. Qualitative Social Work: Research and Practice, 2(1), 61-84.], semi-structured interviews were conducted with kinship foster parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…Thus, according to Kirton et al (2007, p. 8 Building on this theme, several of the survey respondents, and all of those interviewed, reported that managing contact with birth parents was challenging and emotionally stressful because of the complex family relationships involved. This echoed the findings of previous research where tensions in relationships with birth parents were more common in kinship care arrangements compared to non-kinship placements (Coakley et al, 2007;Farmer, 2010;McSherry et al, 2013). The respondents in this study were not explicit about their support needs in relation to contact arrangements but found this to be a difficult and upsetting issue to discuss.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Thus, according to Kirton et al (2007, p. 8 Building on this theme, several of the survey respondents, and all of those interviewed, reported that managing contact with birth parents was challenging and emotionally stressful because of the complex family relationships involved. This echoed the findings of previous research where tensions in relationships with birth parents were more common in kinship care arrangements compared to non-kinship placements (Coakley et al, 2007;Farmer, 2010;McSherry et al, 2013). The respondents in this study were not explicit about their support needs in relation to contact arrangements but found this to be a difficult and upsetting issue to discuss.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, since many kinship placements arise due to a family crisis, carers may not have adequate time, nor the financial and practical resources, to prepare for the imposed changes (Coakley et al, 2007;Palacios and Jimenez, 2009). Moreover, the sense of being ill-prepared, can accentuate stress in the early stages of the placement (Denby, 2011b).…”
Section: Reviewing the Needs Of Kinship Carersmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinship carers can have additional stressors (Whelan, 2003). Often, a child is placed in their care at a time of crisis and they have little or no time to prepare or to make the necessary lifestyle adjustments (Coakley, Cuddeback, Buehler, & Cox, 2007 . In these studies, adopted children's be-haviour is closely associated with their parents' stress levels, with parents of more troubled children experiencing higher levels of stress (Judge, 2003;McGlone et al, 2002).…”
Section: Parenting Stressmentioning
confidence: 99%
“…Buehler, Cox, and Cuddeback (2003) reported that foster parents identified factors such as support from church, a concern for child-wellbeing, tolerance, and strong marriage, flexibility, and routine. Similarly, in examining kinship foster parent's perceptions about successful fostering, Coakley, Cuddeback, Buehler, and Cox (2007) delineated twelve perceived factors that contribute to success. These include faith, good parenting abilities, church involvement and flexibility.…”
Section: Success: Contributing Factorsmentioning
confidence: 99%